Pengembangan Aplikasi Kepegawaian Berbasis Web Menggunakan Framework CodeIgniter Menerapkan Model Waterfall - Zeafli Pebriawan; Isnain, Auliya Rahman (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
This research on developing web-based employee applications was carried out using a case study of BSIP Bandar Lampung with PHP programming, MYSQL and CodeIginter Framework. BSIP (Badan Standardisasi Instrumen Pertanian) is an organization responsible for the standards and quality of agricultural equipment in the area. The main focus of BSIP is to develop standards, conduct quality testing, and supervise the use of agricultural equipment in the sector in Bandar Lampung. In the process of developing web-based applications using the SDLC method, the waterfall model is a useful approach in designing information systems that emphasizes the simplification of stages in system design, making it suitable for use in developing information systems to monitor strategic plans. The development of this application has stages such as analysis, design, programming, and testing by checking the features available in the application. This website-based staffing application has features, namely, adding employee data, editing employee data, printing staffing data, and staffing reports in which there is a feature page for recording leave data for all employees. The data contained in the staffing application is stored in a database contained in the phpMyAdmin program which has been stored in a structured manner based on the data that has been stored in the staffing application. The results of the development are the use case display, activity diagram, and implementation of the program that has been made which displays the results of the login page, admin dashboard page, data input page, employee data, employee attendance report, print employee reports.